Efecto de sincronización bajo la aplicación de benzoato de estradiol más implante y prostaglandina, en vaconas holstein en la provincia de Esmeraldas cantón Esmeraldas parroquia San Mateo - Marquéz Roa, Antonino Hernan (2015)
This research was conducted in the parish of San Mateo, canton Esmeraldas, Esmeraldas province on the Ecuadorian coast to a height of 24 meters to N 0 ° 50 'W and 79 ° 45'. As genetic material 18 vaconas Holstein were evaluated in order to assess the effect of the application synchronization estradiol benzoate plus implant and prostaglandins and establish the cost benefit between treatments. T1: Three treatments were evaluated. More implant estradiol benzoate, T2. More implant prostaglandin and T3. Prostaglandin more more benzoate implant. The treatments were distributed in a complete randomized design (CRD) with six observations and each observation was made up of a cow. The variables studied were: effectiveness rate of estrus synchronization (TEC) and success rate of insemination (TEI). Regarding the first variable all treatments were statistically equal, however, the highest rate of effectiveness of insemination (TEI) was presented by T2. More implant 100%, prostaglandin was also the most profitable a pregnant cow cost $ 40 per pregnant cow, which was incorporated in a recommended herds in the area of Esmeraldas technology.